2002
DOI: 10.1136/gut.50.6.861
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant p16INK4A and DPC4/Smad4 expression in intraductal papillary mucinous tumours of the pancreas is associated with invasive ductal adenocarcinoma

Abstract: Background and aims: Intraductal papillary mucinous tumours (IPMT) of the pancreas constitute a unique pathological entity with an overall incidence of associated invasive malignancy of 20%. The malignant potential of an individual IPMT cannot be accurately predicted. Preoperative estimation of the risk of associated invasive malignancy with IPMT would be of significant clinical benefit. As aberrations in cell cycle regulatory genes are associated with the progression of precursor pancreatic ductal lesions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(123 citation statements)
references
References 24 publications
6
112
1
3
Order By: Relevance
“…The pathogenetic role of CDKN2A/P16 and SMAD4 was further investigated by immunohistochemical analysis. Our results demonstrated that 36% of IPMNs show loss of p16 and 24% of IPMN-related invasive carcinomas loss of Smad4, which is in accordance with previous studies [4,7].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The pathogenetic role of CDKN2A/P16 and SMAD4 was further investigated by immunohistochemical analysis. Our results demonstrated that 36% of IPMNs show loss of p16 and 24% of IPMN-related invasive carcinomas loss of Smad4, which is in accordance with previous studies [4,7].…”
Section: Discussionsupporting
confidence: 81%
“…Immunohistochemistry was used as a surrogate test to assess the involvement of CDKN2A/P16 and SMAD4 genes [7,24,25]. In fact, protein expression may more accurately reflect gene status, as both genes are mainly inactivated by homozygous deletion, and CDKN2A/P16 also by promoter methylation.…”
Section: Evaluation Of Cdkn2a/p16 and Smad4 Dysregulation Using Immunmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 The fact that PanINs show fascin upregulation correlated with histological grade increased our interest in fascin expression in IPMNs, because PanINs and IPMNs share the following fundamental characteristics: 5,6 inherently intraductal; composed predominantly of columnar, mucin-producing cells that may grow in a flat configuration or may produce papillae; exhibit a range of cytologic and architectural atypia (mild, moderate and severe); recognized as precursors to Fascin expression in IPMNs of the pancreas H Yamaguchi et al invasive adenocarcinoma; and sequentially accumulate similar genetic alterations with increasing cytoarchitectural atypia. [43][44][45] We showed that fascin overexpression in IPMNs was correlated with increased histological grade by immunohistochemical analysis, followed by a supporting molecular experiment that showed upregulation of fascin mRNA. We consider that fascin upregulation would be a relatively early event in the progression of IPMN, because of the finding that fascin expression was significantly and almost equally greater in borderline neoplasms (86%) and carcinomas (88%) than in adenomas (51%).…”
Section: Discussionmentioning
confidence: 87%
“…Somatic TP53 mutations are almost exclusively found in areas of high-grade dysplasia or invasion, which indicates that this mutation is a relatively late event in carcinogenesis [88][89][90][91]. Most noninvasive IPMNs show intact expression of the tumor suppressor gene SMAD4, whereas SMAD4 loss can be seen in invasive carcinomas arising in association with IPMNs, again suggesting that SMAD4 is targeted late in neoplastic progression [92,93]. Similarly, loss of p16 is very common in invasive carcinoma arising in association with an IPMN, whereas p16 is preserved in most lower-grade IPMNs [93].…”
Section: Intraductal Papillary Mucinous Neoplasmsmentioning
confidence: 99%